Pendampingan Strategi Pemasaran Berbasis Digital Bagi Pelaku UMKM di Kecamatan Padangsidimpuan Utara - Yusuf Pathuansyahe; Rizky Mery Octavianna; Juwita Handayani; Nursalamah (Jurnal Transformasi Pendidikan Indonesia, 2025)
This study aims to explore the impact of digital marketing strategy assistance on MSME (Micro, Small, and Medium Enterprises) actors in North Padangsidimpuan District. Using a qualitative approach and action research method, the study involved 10 MSME actors who were given intensive training on digital marketing, including the use of social media, e-commerce platforms, and digital analytics tools. The results showed that after the training, there was a significant increase in the understanding of digital marketing among the MSME actors, with 100% of participants being able to use social media as a marketing tool. Additionally, most MSME actors reported a sales increase of up to 40% and successfully expanded their markets beyond the local area. However, challenges remain in content management and digital analytics, indicating the need for ongoing assistance. Overall, the findings suggest that digital marketing can enhance the competitiveness of MSMEs, but proper management and understanding of data analytics are crucial for long-term success.